PREVALENCE OF DENTAL CARIES IN FIRST PERMANENT MOLARS OF CHILDREN BETWEEN 6 TO 9 YEARS OLD ATTENDED AT THE DENTISTRY CLINIC OF THE UNIVERSIDAD TECNOLÓGICA EQUINOCCIAL- SERODU, PERIOD 2016-2017 - Jonathan Ochoa López; Alexander Cruz Gallegos; Leslee Ribadeneira (Kiru)
Objective: Due to the high rate of dental caries in our country, and specifically in the SERODU Clinic, we sought to determine the prevalence of this pathology in permanent first molars, in children aged 6 to 9 years who attended the Clinic of the Faculty of Dentistry from the Equatorial Technological University-Quito-Ecuador and to know which of the first permanent molars has the highest exposure of dental caries, in which gender is more predominant and if there was any previous, preventive or restorative treatment. Materials and methods: An observational, retrospective and descriptive study was conducted in the Clinic of the Faculty of Dentistry of the Technological University Equinoccial-Quito-Ecuador, during the period 2016-2017, reviewing each of the Clinical Histories entered in the interval of proposed time, with a previously calibrated staff. In History the information of the Odontogram and the Treatment section was collected. They met the inclusion and exclusion requirements previously proposed. Results: Of a total of 57 reviewed clinical histories, 44 patients did not present dental caries, while the rest did present the pathology. Sealants being the treatment of choice as prevention in these parts Conclusions: A higher prevalence of dental caries was observed in the first permanent molars of the upper arch. The first upper left molar was the most affected tooth for both genders. The most predominant treatment was the preventive specifically the application of sealants, in both genders.